2017
DOI: 10.1002/pip.2963
|View full text |Cite
|
Sign up to set email alerts
|

Simple pretreatment processes for successful reclamation and remanufacturing of crystalline silicon solar cells

Abstract: This study presents an effective method for recovering unbroken solar cells from photovoltaic (PV) modules. The combustion process is effective at removing ethylene vinyl acetate (EVA) in PV modules. However, the solar cell tends to break during the combustion process. We verify that the breakage mechanisms of the solar cell in the module are related to the thermal changes of EVA during the heat treatment process, that is, generated gases form bubbles behind the glass, and the thermal deformation of the rear E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…The thermal treatment has been reported in several studies as the pretreatment method to remove the EVA binder from waste PV modules 8,9,[26][27][28] and it has been proven to be a better method compared to articial disassembly and organic solvent washing. 29 However, the pyrolysis process is oen overlooked during the recovery of whole PV modules; moreover, the pyrolysis products, reaction mechanisms and pyrolysis characteristics have not been studied in researches.…”
Section: Pyrolysis Product Analysis By Py-gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal treatment has been reported in several studies as the pretreatment method to remove the EVA binder from waste PV modules 8,9,[26][27][28] and it has been proven to be a better method compared to articial disassembly and organic solvent washing. 29 However, the pyrolysis process is oen overlooked during the recovery of whole PV modules; moreover, the pyrolysis products, reaction mechanisms and pyrolysis characteristics have not been studied in researches.…”
Section: Pyrolysis Product Analysis By Py-gc-msmentioning
confidence: 99%
“…Apart from physical separation and organic solvent etching, thermal treatment is mostly used to separate the sandwich structure of crystalline silicon panels and serves as the pretreatment method for recycling silicon wafers. 8,9,[25][26][27][28] Nochang Park et al…”
Section: Introductionmentioning
confidence: 99%
“…In the purification process, PV cells undergo several layers such as p-n junction, antireflection layer, texturization, and aluminum back surface should be removed from silicon for purification. According to the period research, it can be easily divided into two types of reagent ways to purify PV silicon: That containing hydrofluoric acid [5][6][7][8][9][10][11] or not [12][13][14][15][16]. Because HF was indicated as a highly corrosive acid, this study prefers the method without HF.…”
Section: Introductionmentioning
confidence: 99%
“…14,29,34 Recovered silicon can be remelted into SoG-Si (99.9999% purity), with an additional electricity input of 10-20 kWh/module, 15,28 or the silicon wafers can be reused directly if they are recovered intact. 25,[35][36][37] As a result, reusing silicon from EoL modules to replace virgin material can reduce by more than 60% the energy required and greenhouse gas emissions from manufacturing while significantly reducing the metal depletion burden of PV module manufacturing. 25,28 A recent study compared the open-loop and closed-loop models for PV modules; closing the material flow loop was reported to reduce the global warming potential (kg CO 2eq ) by 74%.…”
Section: Introductionmentioning
confidence: 99%
“…23 By 2050, around 2 billion new modules could be manufactured using recovered materials (equivalent to 630 GW), 4 reducing the CO 2eq emissions by 58-117 million tonnes from the PV industry. 38 The previous research has demonstrated the concept of recovering high-purity silicon and using it to remanufacture second-life cells, 16,[35][36][37] Remelt mono Si ingot 16 18.1% (best) 18.5% reference cell wafers into second-life cells with an efficiency improvement from 8% to 14%. 36 In more recent studies, Lee et al demonstrated an efficiency of 18.5% for remanufactured cells using reclaimed monocrystalline (mono) wafers (compared with 18.7% efficiency for the reference cell incorporating commercial silicon wafers), 37 whereas Park et al demonstrated 16.9% remanufactured cell efficiency using reclaimed multicrystalline (multi) wafers (compared with 17.0% efficiency for a reference cell).…”
Section: Introductionmentioning
confidence: 99%